Der Krieg vom Gesichtspunkte naturalisierter Britischer Untertanen - Cohn, August (London : Council of loyal British subjects of German, Austrian or Hungarian birth, 1916)
Bibliotheek Camille Huysmans
Duits
Brochure
Keywords: Wereldoorlog 1